Desain Ruang Pementasan Tertutup yang Responsif terhadap Pandemi Covid-19 - Hersalita, Anak Agung Indira Yufanda; Salain, Putu Rumawan; Susanta, I Nyoman (Jurnal Arsitektur Universitas Udayana; Vol 10 No 02 (2022): Jurnal Arsitektur, Universitas UdayanaDO - 10.24843/jaunud.v10i02.81560, 2022)
The cover stage is an important element in the Cultural Park in Tanjung Benoa, Badung because it can accommodate various artistic and cultural activities. However, the Covid-19 pandemic has greatly affected the comfort and safety of activities in the cover stage. Therefore, the design of the cover stage at the Cultural Park is adjusted to the World Health Organization (WHO) study on aspects of distance, space capacity, air conditioning, the use of touchless technology, the use of ultraviolet light, and the application of copper materials. By considering this study, it is hoped that the design of the cover stage can be responsive to the Covid-19 pandemic and provide a sense of comfort and safety for users.